The Role of the Interleukin-17 Axis and Neutrophils in the Pathogenesis of Endemic and Systemic Mycoses - Puerta-Arias, Juan David; Mejía, Susana P.; González, Ángel (Frontiers in Cellular and Infection Microbiology, 2020)
Systemic and endemic mycoses are considered life-threatening respiratory diseases which are caused by a group of dimorphic fungal pathogens belonging to the genera Histoplasma, Coccidioides, Blastomyces, Paracoccidioides, Talaromyces, and the newly described pathogen Emergomyces. T-cell mediated immunity, mainly T helper (Th)1 and Th17 responses, are essential for protection against these dimorphic fungi; thus, IL-17 production is associated with neutrophil and macrophage recruitment at the site of infection accompanied by chemokines and proinflammatory cytokines production, a mechanism that is mediated by some pattern recognition receptors (PRRs), including Dectin-1, Dectine-2, TLRs, Mannose receptor (MR), Galectin-3 and NLPR3, and the adaptor molecules caspase adaptor recruitment domain family member 9 (Card9), and myeloid differentiation factor 88 (MyD88). However, these PRRs play distinctly different roles for each pathogen. Furthermore, neutrophils have been confirmed as a source of IL-17, and different neutrophil subsets and neutrophil extracellular traps (NETs) have also been described as participating in the inflammatory process in these fungal infections. However, both the Th17/IL-17 axis and neutrophils appear to play different roles, being beneficial mediating fungal controls or detrimental promoting disease pathologies depending on the fungal agent. This review will focus on highlighting the role of the IL-17 axis and neutrophils in the main endemic and systemic mycoses: histoplasmosis, coccidioidomycosis, blastomycosis, and paracoccidioidomycosis.